IMPLEMENTASI MODEL PENILAIAN DINAMIS DALAM PERKULIAHAN DI PROGRAM STUDI PENDIDIKAN BAHASA INDONESIA - Sastromiharjo, Andoyo; Mulyati, Yeti; Regina, Frilia Shantika; Lubis, Fitriani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The aim of this research is to determine the application of the dynamic assessment model in the Indonesian Language Education Study Program. Assessment applied in the field of education seeks to provide an overview of students' understanding processes and skills in obtaining information so that the resulting assessment is not only in the form of numbers, but also a description of follow-up plans that educators can carry out so that assessment becomes an evaluation tool (indicator) in achieving learning goals. This research uses quantitative research with descriptive methods. The population of this research is the Indonesian Language Education Study Program at three universities, namely Medan State University (Unimed), Indonesian Education University (UPI), and Pasundan University. The samples from this research were two to three lectures in each study program. Data collection techniques use observation techniques. This data analysis step uses data presentation in visual form to see the application of the dynamic assessment model in the lecture process. The research results obtained (1) most lecturers had carried out an implicit initial assessment process in the opening or initial activities; (2) the core activities have been carried out by some lecturers by applying the principles of the dynamic assessment model by giving students the opportunity to submit arguments and provide feedback by lecturers to be able to provide confirmation of student understanding. Apart from that, the documented question and answer process has been carried out by the lecturer as a form of assessment of the process carried out by the learning process; (3) lecturers have carried out closing activities according to the indicators observed, although some lecturers missed carrying out reflection activities and missed assessing according to the assessment rubric. So, it can be concluded that lecturers have not maximized the final assessment in each learning process.